2014
DOI: 10.1016/j.bcp.2014.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the contribution of CYP2J2 to ritonavir metabolism in vitro and in vivo

Abstract: Ritonavir, an HIV protease inhibitor, is successfully used for the prevention and treatment of HIV infections. Ritonavir pharmacokinetics are complicated by inhibition, induction and pharmacogenetics of cytochrome P450 (CYP) enzymes mediating its clearance. This investigation revealed that CYP2J2, along with CYP3A4/5 and CYP2D6, efficiently metabolizes ritonavir, and to a CYP2J2-specific (minor) metabolite. Chemical inhibition of ritonavir metabolism, clearance, KI/kinact and abundance of CYP2J2 in liver micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Recent studies report that CYP2J2 also plays a role in the biotransformation of xenobiotics, including drugs such as albendazole (Wu et al, 2013b), astemizole (Matsumoto et al, 2002), apixaban (Wang et al, 2010), ebastine (Liu et al, 2006), fenbendazole (Wu et al, 2013b), ritonavir (Kaspera et al, 2014), and terfenadine (Lafite et al, 2006). Using strong chemical inhibitors to inhibit the biotransformation activity of recombinant P450 isoforms or human liver microsomes is a valuable method for P450 reaction phenotyping studies to characterize the enzymes responsible for drug metabolism (Rodrigues, 1999;Yoon and Liu, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies report that CYP2J2 also plays a role in the biotransformation of xenobiotics, including drugs such as albendazole (Wu et al, 2013b), astemizole (Matsumoto et al, 2002), apixaban (Wang et al, 2010), ebastine (Liu et al, 2006), fenbendazole (Wu et al, 2013b), ritonavir (Kaspera et al, 2014), and terfenadine (Lafite et al, 2006). Using strong chemical inhibitors to inhibit the biotransformation activity of recombinant P450 isoforms or human liver microsomes is a valuable method for P450 reaction phenotyping studies to characterize the enzymes responsible for drug metabolism (Rodrigues, 1999;Yoon and Liu, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Heterologously expressed enzyme CYP2J2 was the only CYP, other than CYP2D6, to form 4-OH-ATX, albeit with rates 100-fold lower than CYP2D6. Hepatic abundance of CYP2J2 is low, but its importance may be relevant in individuals who have low CYP2D6 activity, as with the anti-viral drug ritonavir (Kaspera et al, 2014). Studies using specific chemical inhibitors of CYPs in the HLM sample genotyped as an intermediate metabolizer (AS = 0.5) found that CYP2D6 and CYP2E1 were the major isoforms involved in 4-OH-ATX formation.…”
Section: Discussionmentioning
confidence: 99%
“…Efavirenz and ritonavir are pre‐validated compounds developed by Simcyp and included in the Simcyp Simulator® compound library. The ritonavir compound file has been widely used as a CYP3A4 inhibitor in mechanistic modelling (Colbers, Greupink, Litjens, Burger, & Russel, ; Hyland, Dickins, Collins, Jones, & Jones, ; Kaspera et al, ; Marsousi et al, ; Wang, ), and compound‐specific parameters and validation data for the use of efavirenz as a CYP3A4 and 2B6 inducer within the Simcyp Simulator®, have recently been published (Ke, Barter, Rowland‐Yeo, & Almond, ).…”
Section: Methodsmentioning
confidence: 99%